Development of a Financial Framework for the National Plan for Regional Development: The Evidence from Serbia. - Vukovic, Darko Bozha; Radulovic, Dejan; Markovic, Milos; Kochetkov, Dmitry Mikhaylovich; Vlasova, Natalya Yuryevna (Economy of Regions, 2017)
The aim of this paper is to examine the development of a financial framework for assessing the effectiveness of interventions. The research is based on the evidence from Serbia. In terms of methods applied, we used econometric and scenario analysis. We presented - as individual separate items - the issues such as “who” - Government budget (Ministry, specific program, loan, donor, etc.), “how much” - the amount spent, “where” (NUTS 2 region), and on “what” (type of initiative). In our model, each of the interventions applied to one of the regional development priorities is linked and evaluated by its effectiveness observing the performance of the group of indicators associated with each of the priorities. All data obtained from 8 sectors were categorized under 4 priorities, i.e. “People, Place, Productive Capacity, and Institutional Capacity”. Accordingly, we evaluate the effectiveness by observing the performance of a group of indicators related to each of the priorities. Our recommendations for optimizing the distribution structure of regional policies and regions are determined by the analysis of the performance of the group of indicators and their relative rankings per NUTS 2 region. The results are significant for further theoretical and applied research, as well as decision-making in the field of government financial policy. Our results confirmed that calculations of funds for regional development in strategic areas appear to be slightly problematic because, in the past, there was no strategic distribution based on established facts, which could be measured in terms of performance.